2021
DOI: 10.1172/jci.insight.141299
|View full text |Cite
|
Sign up to set email alerts
|

Ciclopirox olamine induces ferritinophagy and reduces cyst burden in polycystic kidney disease

Abstract: Despite the recent launch of Tolvaptan, the search for safer polycystic kidney disease (PKD) drugs continues. Ciclopirox (CPX) or its olamine salt (CPX-O) are contained in number of commercially available antifungal agents. CPX is also reported to possess anticancer activity. Several mechanisms of action have been proposed including chelation of iron and inhibition of iron dependent enzymes. Here, we show that CPX-O inhibited in vitro cystogenesis of primary human PKD cyst-lining epithelial cells cultured in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 69 publications
(101 reference statements)
1
12
0
4
Order By: Relevance
“…The olamine salt of ciclopirox (CPX-O) induces NCOA4-mediated ferritinophagy and ferritin degradation, resulting in the inhibition of cyst growth and the amelioration of murine polycystic kidney disease [127].…”
Section: Box 3 Risks Of Ferritinophagy Inhibitionmentioning
confidence: 99%
“…The olamine salt of ciclopirox (CPX-O) induces NCOA4-mediated ferritinophagy and ferritin degradation, resulting in the inhibition of cyst growth and the amelioration of murine polycystic kidney disease [127].…”
Section: Box 3 Risks Of Ferritinophagy Inhibitionmentioning
confidence: 99%
“…It has also been reported that Ferritin is markedly elevated in cystic kidneys of PKD mice [118]. Treatment with ciclopirox olamine (CPX-O), an iron chelator, inhibited ferritin accumulation in ADPKD kidneys and induced ferritinophagy in an iron-independent manner, resulting in the reduction in cyst growth in PKD mice [118]. These studies support that targeting ferroptosis may be a novel therapeutic strategy for ADPKD treatment.…”
Section: Targeting Ferroptosis For Kidney Disease Therapymentioning
confidence: 72%
“…We recently reported that treatment with ferroptosis inhibitor, Fer-1, delayed cyst growth in both early-stage and long-lasting ADPKD mouse models [15]. It has also been reported that Ferritin is markedly elevated in cystic kidneys of PKD mice [118]. Treatment with ciclopirox olamine (CPX-O), an iron chelator, inhibited ferritin accumulation in ADPKD kidneys and induced ferritinophagy in an iron-independent manner, resulting in the reduction in cyst growth in PKD mice [118].…”
Section: Targeting Ferroptosis For Kidney Disease Therapymentioning
confidence: 97%
“…The role of DFO or DFX also inhibited the progression of inflammation and fibrosis in CKD (Naito et al, 2015; Zhou et al, 2022). CPX‐O, an olamine salt form of CPX, was able to reach the urinary tract, it might be a candidate for the treatment of PKD by chelating iron and preventing iron‐dependent enzymes (Radadiya et al, 2021). ISL restrained accumulation of lipid peroxidation products and labile iron in septic‐triggered AKI by attenuating ferritinophagy‐promoted ferroptosis (Tang et al, 2021).…”
Section: Therapy In Kidney Disease Targeting Ferroptosismentioning
confidence: 99%